Adaptation and Validation of the Polish Version of the 10-Item Mobile Phone Problematic Use Scale - Mach, Anna; Demkow-Jania, Marta; Klimkiewicz, Anna; Jakubczyk, Andrzej; Abramowska, Małgorzata; Kuciak, Anna; Serafin, Piotr; Szczypiński, Jan; Wojnar, Marcin (Frontiers in Psychiatry, 2020)
Pathological use of smartphones may be the biggest non-drug addiction of the 21st century. Therefore, short screening tools designed for easy identification of people with problematic mobile phone use are needed. The main aim of present study was to validate a short version of the Mobile Phone Problematic Use Scale (MPPUS-10) in the Polish population. The study comprised 640 university students aged 18-38 years. We used the self-report questionnaire which included questions regarding socio-demographic variables and Polish versions of the Mobile Phone Problem Use Scale (MPPUS-10), Mobile Phone Addiction Assessment Questionnaire (MPAAQ in Polish KBUTK) and Internet Addiction Test (IAT) by Kimberly Young. Analysis showed high reliability of the final Polish version (Cronbach’s α = 0.78) and confirmed significant correlation between the MPPUS-10 and the previously used in Poland MPAAQ (rho = 0.56; p < 0.001). Due to the poor correlation of the item number 10 with other items, we suggest dropping the item 10 and using the 9-item Polish version. Our result also confirmed significant correlation between the MPPUS-10 and the IAT (rho = 0.54; p < 0.001). The result of the study is the Polish validation and adaptation of the MPPUS-10 scale with confirmed psychometric values. It provides a short and convenient screening tool to assess the problematic mobile phone use. Our results also indicate the need for revision of available diagnostic tools in Poland.